Comprehensive Gene Expression Analysis and Identification of Stat-1 as Master Regulator in Oral Squamous Cell Carcinoma - S.S. , Ariya; Rachel James, Akhila; Joseph, Baby (International Journal of Psychosocial Rehabilitation, 2020)
Gene expression profiling and analysis help in the identification of master regulators inducing disease. The GEO dataset GSE74530, comprising samples from 6 normal and 6 oral cancer patients, was analyzed using the R package of the Bioconductor program GEO2R. The differentially expressed genes among the samples were identified using the Benjamini-Hochberg method. The up-regulated and down-regulated genes were identified based on fc value > 2.0 and p-value < 0.5. A protein interaction network was constructed for the up-regulated and down-regulated genes with data from the BioGrid and Reactome databases. The network was further explored by applying mathematical models for topological interaction analysis to determine the hub genes. Signal transducer and activator of transcription 1 (STAT1) was identified as the master regulator of oral squamous cell carcinoma (OSCC). Cross-validation with the Cancer Genome Atlas (TCGA) followed by gene ontology and functional enrichment analysis also revealed the role of STAT1 in the progression of OSCC. Survival analysis with respect to expression of gene also showed the decrease in rate of patient prognosis with increase in expression of STAT1.